Ergonomics in Work Method to Improve Construction Labor Productivity - Tuti Sumarningsih; Mochammad Agung Wibowo; Sri Prabandiyani Retno Wardani (Chemical Engineering Diponegoro University, 2016)
Productivity is an important issue in the construction industry. It is directly related to the construction cost and duration of the work. Construction productivity is influenced by many factors, such as material, equipment and labor. Labor is the most important factor, since labor determines how the work is done. Labor productivity is influenced by the work methods, physical fatigue, work environment, capability, and complexity of the work. To improve labor productivity due to the work method, application of the principle of ergonomics is important to consider. This research was held in Yogyakarta included 10 construction projects and involve 30 labor of brick masonry work, 22 labor of ceramic instalation, and 24 labor of wall painting work. The application of ergonomics principles in the masonry work, plaster work, ceramic installation, and wall painting work show an increase in labor productivity by 28.49%, 16.22%, 21.47%, and 26.18% respectively. Compared with the National Standards of Indonesia (NSI) these productivity per job are higher by 10.34%, 57.89%, 12.72%, and 33.33%.